Vitamin D Metabolic Pathway Genes Polymorphisms and Their Methylation Levels in Association With Rheumatoid Arthritis - Tian-Ping Zhang (Frontiers Media S.A., 2021)
Abnormal vitamin D metabolism is involved in the pathogenesis of rheumatoid arthritis (RA). In this study, we evaluated the association of single nucleotide polymorphisms (SNPs) and methylation levels in vitamin D metabolic pathway genes with RA susceptibility. Ten SNPs in vitamin D metabolic pathway genes (CYP2R1, CYP24A1, VDR, CYP27B1) were genotyped in 477 RA patients and 496 controls by improved multiple ligase detection reaction (iMLDR). The methylation levels of the promoter regions of these genes were detected in 122 RA patients and 123 controls using Illumina Hiseq platform. We found that the CYP2R1 rs1993116 GA genotype, CYP27B1 rs4646536 GA genotype, rs4646536 A allele frequencies were significantly increased in RA patients when compared to controls. The decreased risk of rs1993116, rs4646536 was found under the dominant mode in RA patients. However, no significant association was found between CYP2R1 rs7936142, rs12794714, CYP24A1 rs2762934, rs6068816, rs2296239, rs2296241, VDR rs11574129, rs3847987 polymorphism, and RA susceptibility. The VDR, CYP27B1 methylation levels in RA patients were significantly lower than those in controls, while CYP2R1, CYP24A1 methylation levels were not associated with RA. There were no statistical associations between CYP2R1, CYP24A1, VDR, CYP27B1 methylation levels and their respective genotype in RA patients. In addition, plasma 25OHD level in RA patients was significantly lower than that in healthy controls. In summary, our results showed that CYP2R1, CYP27B1 genetic variations were associated with the genetic background of RA, while altered VDR, CYP27B1 methylation levels were related to the risk of RA.